ZnO Nanowire‐Based Early Detection of SARS‐CoV‐2 Antibody Responses in Asymptomatic Patients with COVID‐19. Issue 14 (5th February 2022) - Kim, Jung; Lee, Sung Kyun; Lee, Jong‐Hwan; Kim, Hye‐Yeon; Kim, Nam Hoon; Lee, Chang Hoon; Lee, Chang‐Seop; Kim, Hong Gi
Abstract: A serological immunoassay based on enzyme‐linked immunosorbent assay (ELISA) is a crucial tool for screening and identification of human SARS‐CoV‐2 seroconversion. Various immunoassays are developed to detect the spike 1 (S1) and nucleocapsid (NP) proteins of SARS‐CoV‐2; however, these serological tests have low sensitivity. Here, a novel microplate (MP) is developed on which a ZnO nanowire (NW) is fabricated by a modified hydrothermal synthesis method. This plate is coated with SARS‐CoV‐2 NP and used as a fluorescent immunoassay (FIA) to detect antibodies specific for SARS‐CoV‐2 NP. Compared with the bare MP, the ZnO‐NW MP binds high levels (up to 5 µg mL −1 ) of SARS‐CoV‐2 NP tagged to histidine without any surface treatment. A novel serological assay based on the ZnO‐NW MP is more sensitive than a commercial immunoassay, enabling early detection (within <5 days of a reverse transcription polymerase chain reaction‐confirmed COVID‐19 infection) of anti‐SARS‐CoV‐2 NP IgG antibodies in asymptomatic patients with COVID‐19. This is the first assay to detect early antibody responses to SARS‐CoV‐2 in asymptomatic patients. Therefore, this serological assay will facilitate accurate diagnosis of COVID‐19, as well as estimation of COVID‐19 prevalence and incidence. Abstract : A novel microplate (MP) on which a ZnO nanowire (NW) is fabricated by a modified hydrothermal synthesis method to detect antibodies specific for SARS‐CoV‐2 NP antigen is presented. A novel serological assay based on the ZnO‐NW MP is more sensitive than a commercial immunoassay, enabling early detection of anti‐SARS‐CoV‐2 NP IgG antibodies in asymptomatic patients with COVID‐19.